2016
DOI: 10.1007/s12576-016-0508-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of type 2 diabetes on brain glycometabolism in rats: focus on glycogen and monocarboxylate transporter 2

Abstract: Astrocyte-neuron lactate shuttle (ANLS) is a pathway that supplies glycogen-derived lactate to active neurons via monocarboxylate transporter 2 (MCT2), and is important for maintaining brain functions. Our study revealed alterations of ANLS with hippocampal hyper-glycogen levels and downregulated MCT2 protein levels underlying hippocampal dysfunctions as a complication in type 2 diabetic (T2DM) animals. Since T2DM rats exhibit brain dysfunctions involving several brain regions, we examined whether there might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…16,17 MCT4 expression is not altered. 16 The effect on GLUT1 seems inconsistent, with some studies reporting upregulation and others finding no alteration. 46,47 Similar to the results of the present study, MCT1 expression is upregulated and GLUT3 expression remains unaltered in the mature hippocampus.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…16,17 MCT4 expression is not altered. 16 The effect on GLUT1 seems inconsistent, with some studies reporting upregulation and others finding no alteration. 46,47 Similar to the results of the present study, MCT1 expression is upregulated and GLUT3 expression remains unaltered in the mature hippocampus.…”
Section: Discussionmentioning
confidence: 89%
“…Oxidative stress and inflammation may negatively influence hippocampal dendritogenesis and function. Furthermore, in adult rats, hyperglycemia alters glycogen and lactate metabolism in the hippocampus . Astrocytic glycogen breakdown and astrocyte‐neuron‐lactate transport has an important role in hippocampal synaptic morphology and plasticity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on brain glycogen in diabetes is somewhat confounding. For instance, a rat model of type 2 diabetes (Otsuka Long-Evans Tokushima Fatty rat: OLETF) have been reported to accumulate ~30% higher amounts of glycogen in the hippocampus (Shima et al, 2017) while brain stem glycogen levels remain similar (Shima, Jesmin, Matsui, Soya, & Soya, 2018). Another type 2 diabetes model rat strain (Zucker Diabetic Fatty rat: ZDF) was reported to have a tendency for decreased hippocampal glycogen levels (Shima et al, 2017;Sickmann, Waagepetersen, Schousboe, Benie, & Bouman, 2010).…”
Section: ;mentioning
confidence: 99%
“…Exercise results in increased serotonin turnover, which may promote glycogenolysis (Matsui et al, 2015). The same group have reported that type 2 diabetic patients had higher glycogen in the hippocampus, hypothalamus and cortex, and that MCT2 protein levels decreased, suggesting less efficient lactate shuttling (Shima et al, 2016). This effect has been correlated with exercise, which was shown to increase glycogen levels, MCT2 expression and improve cognitive performance.…”
Section: Glycogen and Exercisementioning
confidence: 99%